Knowledge of routes of transmission, attitudes and prevention measures of COVID-19 in medical students of the Universidad Nacional del Nordeste - Vargas Capará, Facundo (2020)
Introduction: In 2020, the COVID-19 pandemic emerged, caused by SARS-CoV-2, associated with higher morbidity and mortality, impacting the lives of the world population. Objective: Determine knowledge of transmission routes, prevention measures and attitudes about COVID-19 in 5th and 6th year students of the Facultad de Medicina of the Universidad Nacional del Nordeste in the months of May to June 2020. Methods: A descriptive, cross-sectional study was carried out with the students of the last years of the Medicine career. The instrument was validated by expert judgment. A pre-designed ad hoc questionnaire was used through the Google Forms platform. The data were analyzed using Epi Info version 7 software. Results: A total of 153 surveys were analyzed (N = 153). The mean age was 24.8 years. 42% of the students surveyed refer to information about talks with doctors, 15% through social networks, television channels and blogs and the remaining 13% do so through friends and / or family. 95.4% of the population studied had changes in attitude, increasing the way of cleaning / disinfecting surfaces and environments. 70% responded that it is through the air (Flügge Drops), while talking, coughing or sneezing as the most frequent route of infection. 84.4% mention being calm, 13% are nervous and worried and 2.6% tired. Conclusion: Adequate knowledge and positive attitudes are found in the studied population.